Pengaruh Kualitas Pelayanan Publik, Sarana Prasarana Publik Dan Kinerja Pegawai Terhadap Kepuasan Masyarakat Pada Pelayanan E-KTP Di Kantor Camat Ampek Angkek Kabupaten Agam - Febri Suci, Arfita; Ajidin, Asep (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2023)
This study aims to determine and analyze the effect of the quality of public services, public infrastructure and employee performance on community satisfaction in the E-KTP service at the Ampek Angkek Sub-District Office, Agam Regency. This type of research is associative descriptive analysis. The population in this study is all people who manage E-KTP who have not recorded their E-KTP. The sample used was 100 people who took care of the E-KTP and used a proportional random sampling technique. Primary data is the type of data used in this study. Data processing using SPSS 24. Data collection techniques using a questionnaire. The collected data was examined using descriptive analysis. Multiple regression analysis in research. Based on the research findings, it is known that the quality of public services (X1) is 0.017 <0.05. The significance of facilities and infrastructure (X2) is 0.024 <0.05 and employee performance (X3) is 0.000 <0.05 (Ho is rejected Ha is accepted). This illustrates that employee performance has a significant influence on community satisfaction managing e-KTP services at the Ampek Angkek Sub-District Office.